Selecting cold 2n transfer in 162Dy(116Sn,118Sn)160Dy - Härtlein, T.; Bauer, H.; Pansegrau, D.; Schwalm, Dirk (The European physical journal. A, Hadrons and nuclei, 1999)
Cold 2n transfer has been studied using the reaction 162Dy(116Sn,118Sn)160Dy at energies in the vicinity of the Coulomb barrier. The experiment was performed at the Heidelberg-Darmstadt Crystal Ball spectrometer which was extended by 6 Compton suppressed Ge-detectors. It is demonstrated, that the direct population of intrinsically cold states in the deformed 160Dy transfer product can be selected by identifying and suppressing excitations to states above the yrast line using the Crystal Ball. The probability for populating yrast states in the deformed 160Dy nuclei in a 2n transfer reaction increases from 7% at grazing collisions up to ≈ 50% at large impact parameters, while the probability for populating the ground state in the spherical 2n transfer product 118Sn stays about constant at ≈ 45% for all measured impact parameters.